Thyroid Stimulating but Not Blocking Autoantibodies Are Highly Prevalent in Severe and Active Thyroid-Associated Orbitopathy: A Prospective Study - E. Kampmann; T. Diana; M. Kanitz; D. Hoppe; G. J. Kahaly (International Journal of Endocrinology)
The clinical utility of the functional TSH receptor autoantibodies was prospectively evaluated in patients with thyroid-associated orbitopathy (TAO). Ophthalmic, endocrine, and serological investigations were performed in 101 consecutive patients with severe and active TAO. Serum thyroid stimulating (TSAb) and blocking (TBAb) antibody levels were measured with two bioassays using cells that express a chimeric TSH receptor and CRE-dependent luciferase. TSAb results are expressed as percentage of specimen-to-reference ratio (SRR %). Blocking activity is defined as percent inhibition of luciferase expression relative to induction with bovine TSH alone. All 101 consecutively followed-up patients with severe and active TAO were TBAb negative. In contrast, 91 (90%) were TSAb positive of whom 90 had Graves’ disease. Serum TSAb levels correlated with the diplopia score (P=0.016), total severity eye score (P=0.009), proptosis (P=0.007), lid aperture (P=0.003), upper lid retraction (P=0.006), keratopathy (P=0.04), and thyroid binding inhibiting immunoglobulins (TBII, P<0.001) and negatively with the duration of TAO (P=0.002). Median serum values of TSAb were SRR% 418 (range 28% to 795%). TSAb, not TBAb, are highly prevalent in severe/active TAO and serum TSAb levels correlate with clinical disease severity.